PEMBELAJARAN MENULIS TEKS PERSUASI PADA SISWA KELAS VIII SMP NEGERI 6 PONTIANAK DI MASA PEMBELAJARAN DARING - Evi Elianti; Martono Martono; Nanang Heryana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This thesis background by a general problem, namely “How is learning to write persuasive texts for class VIII students of SMP Negeri 6 Pontianak in the 2021/2022 academic year?”. The purpose of this study is to describe the problem, while this research is useful for researchers to increase knowledge and insight in analyzing persuasive text learning, it can be used by teachers and students as learning media and as comparison material for other research, this thesis uses descriptive methods, research forms qualitative. Therefore, the results of data analysis can be concluded that learning to write persuasive texts for class VIII students of SMP Negeri 6 Pontianak in terms of learning planning is categorized as being in accordance with the score (3) the reason is that the teacher is in accordance with the learning planning guidelines. Then the implementation of categorized learning is in accordance with the score (3) because the teacher is able to carry out learning in accordance with the implementation guidelines for teaching teachers. The results of learning to write persuasive texts carried out by students seen from the content aspect are categorized (very capable) with a score of (3), from the structural aspect it is categorized (capable) with a score of (2), and from the aspect of linguistic rules it is categorized (enough) with a score of (1 ). The author hopes that this research can be continued by further researchers to do research from others.